Application of Expert Systems Theoretical and Practical Aspects - Nunes da Silva, Ivan; Andrade Flauzino, Rogério (IntechOpen, 2020)
What are expert systems and what are their purposes? What are the impacts resulting from their implementations? This book aims to answer these questions and more. Written by experts in the field, chapters It explores different concepts of expert systems such as computational intelligence, signal processing, real time systems, systems optimization, electric power systems, fault diagnosis, asset management, and smart cityescities. This book will appeal to wide range of readers, including those interested in acquiring basic knowledge and those who are motivated to learn more about the technical elements and technological applications of expert systems.